STMO-07 Adverse events related to the glioblastoma surgery and their perioperative management in our hospital. (28th November 2020) - Kashiwagi, Hideki; Kawabata, Shinji; Kimura, Seigo; Yagi, Ryokichi; Ikeda, Naokado; Nonoguchi, Naosuke; Furuse, Motomasa; Wanibuchi, Masahiko
Abstract: Background: The standard treatment for glioblastoma is surgical resection following chemoradiation therapy. The rate of removal or the amount of residual tumor has some impact on the prognosis of patients with glioblastoma, but the highly invasive nature of this tumor makes complete removal limited to the contrast-enhanced lesions difficult due to its localization. Furthermore, when postoperative seizures and venous thrombosis are included in surgery-related complications, these perioperative adverse events can cause delays in the initiation of chemoradiotherapy and delay the return to work and home, such as prolonged hospitalization and rehabilitation time. Methods: We retrospectively reviewed the perioperative status of the recent 50 consecutive cases with histologically confirmed as glioblastoma at our hospital, the patient background, tumor localization, and perioperative treatment, and so on. Results: The major perioperative complications were ischemic or hemorrhagic complications, epileptic seizures, venous thrombosis, and pneumonia; CTCAE grade 2 or higher, grade 3 or higher, and grade 4 occurred in about 40%, 20%, and 10%, respectively, with some patients having multiple complications. Discussion: Although there was a tendency for ischemic changes around the cavity of the resection as the resection rate increased, most cases were asymptomatic and it seemed to be acceptable if residual brain function could be preserved. Residual tumors tended to show hemorrhagic changes and epileptic seizures because this is thought to be that the tumor was deliberately left in place to preserve function, based on the localization of the tumor. Postoperative FDP levels were useful in predicting the development of deep vein thrombosis and pulmonary artery thromboembolism. Conclusion: Because glioblastoma has short survival time and patient PS before and after surgery varies greatly depending on tumor localization, it is important to consider risk-benefit strategies for each case and to establish a scheme for a seamless transition from perioperative management to the introduction of postoperative therapy and maintenance therapy.